Biofilm formation to inhibition: role of zinc oxide-based nanoparticles - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Badiger, Manohar V.; Patel, Pratikshkumar R.; Thorat-Gadgil, Bhagyashi S.; Pandit, Abhay; Bohara, Raghvendra A. (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Zinc oxide nanoparticles have received much attention worldwide as they possess unique properties like varied morphology, large surface area to volume ratio, potent antibacterial activity, and biocompatibility. Biofilm contains homogenous or heterogeneous microorganisms that remain enclosed in a matrix of an extracellular polymeric substance on biotic or abiotic surfaces. Bacterial biofilm formed on medical devices such as central venous catheters, urinary catheters, prosthetic joints, cardiovascular implantable devices, dental implants, contact lenses, intrauterine contraceptive devices and breast implants cause persistent infections. Such biofilm-associated infections in medical implants cause serious problems for public health and affect the function of medical implants. So, there is an urgent need for the use of an antimicrobial agent that will inhibit biofilm, including such antibiotic-resistant bacterial strains as bacteria, to develop multiple drug-resistances resulting in failure of the antibiotic's action. The antimicrobial agent used should be ideal in terms of biocompatibility, antimicrobial activity, stability at different environmental conditions, with less sensitivity to the development of resistance towards micro-organisms, safe for in vivo and in vitro use, and remain non-hazardous to the environment, etc. The first objective of the review discusses the insights into the formation of biofilm on a medical device with the current strategies to inhibit. The second purpose is to review the recent progress in ZnO- based nanostructure including composites for antibacterial and anti-biofilm activities. This will offer a new opportunity for the application of Zinc oxide-based material in the prevention of biofilm on the medical devices.
Keywords: antibacterial activity; Antibiofilm agent; Biocompatibility; Biofilm; Nanocomposites; ZnO nanoparticles

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics

Characterization of a novel Tequatrovirus phage from pristine stretch of the Ganges River, India, in reducing bacterial load from sewage water - Samson, Rachel; Pawar, Ameya; Khairnar, Krishna; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2025)
Effective treatment of wastewater (WW) and its reuse is necessary to meet certain sustainable development goals and a circular economy. Escherichia coli is one of the primary contaminants in the WW, and its extra-intestinal occurrence poses a considerable threat under one health. This study is the first report of a novel broadspectrum phage (& fcy;ERS-1) isolated from a pristine stretch of the Ganges River in the biocontrol of E. coli, resistant to 3rd-and 4th generation cephalosporins and aztreonam. This is the first report of a phage from the Tequatrovirus genus to infect P. aeruginosa. The & fcy;ERS-1 could reduce the abundance of E. coli cells by 8.22 log10 CFU/mL <= 24 hrs. Additionally, phi ERS-1 disrupted the biofilm of E. coli with a reduction of 3.88 log10 CFU/mL. Further, phi ERS-1 could inhibit biofilm by multiple strains of E. coli (ATCC 8739, 25922, 43888) and multiple generaincluding E. coli ATCC 8739, Shigella boydii ATCC 9207, P. aeruginosa (ATCC 9027). The phage phi ERS-1 reduced bacterial counts in raw WW by 2 log10 CFU/mL and 4 log10 CFU/mL reduction in coliform-enriched WW in <= 24 hours. Overall, this study suggests that phi ERS-1 could be used as an effective alternative to be combined with other treatments for improving the quality of WW disposal and environmental health by reducing the bacterial load.
Keywords: Antibiofouling; Biofilm; Coliform; Ganges; Green approach; Phages; wastewater